Exploring Consumer Behavior, Logistics Challenges, and Technological Innovations in Online Grocery Shopping: A Comprehensive Review - Vaja, Hitarthsinh; Monpara, Yesha; Gafurjiwala, Moh. Kaif; Parchani, Nilesh; Chauhan, Rahul; Maseleno, Andino (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This study examines consumer behavior, satisfaction, and loyalty in online grocery shopping in Ahmedabad, India, following the COVID-19 pandemic. Employing a quantitative approach, data was collected from 122 respondents through structured surveys to assess the role of demographic factors, logistics, and technological innovations in shaping consumer experiences. ANOVA analyses revealed that while age and gender generally do not significantly influence online shopping behavior, specific factors do show demographic variances, indicating nuanced preferences among different consumer groups. Findings demonstrate that consumer adoption of online grocery shopping is driven by preferences and technological advancements, whereas logistics challenges negatively impact satisfaction and loyalty. These insights underscore the need for grocery retailers to enhance logistics services and leverage technology to cater to diverse customer needs. The study’s implications extend globally, as online grocery shopping grows worldwide, offering potential for retailers to optimize customer engagement through innovative solutions.